Tribology in machine design - Stolarski, T. A. (Butterworth Heinemann, 2000)
""Tribology in Machine Design is strongly recommended for machine designers, and engineers and scientists interested in tribology. It should be in the engineering library of companies producing mechanical equipment.""Applied Mechanics ReviewTribology in Machine Design explains the role of tribology in the design of machine elements. It shows how algorithms developed from the basic principles of tribology can be used in a range of practical applications within mechanical devices and systems. The computer offers today's designer the possibility of greater stringen.
Originally published: Oxford : Heinemann Newnes, 1990.
Keywords: Machine design.; Tribology.; elektronické knihy; electronic books